2013
DOI: 10.1186/2193-1801-2-232
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression responses in Suaeda salsa after cadmium exposure

Abstract: Coastal line is now polluted by many kinds of sewage including heavy metals discharged by intensive human activities. Cadmium is a nonessential heavy metal for organisms and can cause many kinds of adverse effect on the organisms. Suaeda salsa, a pioneer halophyte in intertidal zone of the Bohai coast, was proved to have cadmium-tolerant capacity. Given that, S. salsa was suggested as a potential coastal bio-indicator plant for cadmium contamination in the intertidal zone. Therefore, it is essential to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Cadmium increased the expression of CAT1, GST and Prx Q genes coding for enzymes involved in antioxidant activities (Cong et al, 2013). Wu et al (2013) observed that only CAT gene expression levels significantly increased in response to Zn, Pb or the combination of both metals in shoots of Suaeda salsa, while activities of the antioxidant enzymes SOD, glutathione peroxidase (GPx) and catalase (CAT) increased in response to Zn and Zn þ Pb.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium increased the expression of CAT1, GST and Prx Q genes coding for enzymes involved in antioxidant activities (Cong et al, 2013). Wu et al (2013) observed that only CAT gene expression levels significantly increased in response to Zn, Pb or the combination of both metals in shoots of Suaeda salsa, while activities of the antioxidant enzymes SOD, glutathione peroxidase (GPx) and catalase (CAT) increased in response to Zn and Zn þ Pb.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In response to Cd, myo-inositol-1-phosphate synthase (MIPS) transcripts are clearly up-regulated in leaves of Suaeda salsa. Given that MIPS is a pivotal enzyme that catalyses myo-inositol synthesis, metabolic products of which (such as myo-inositol hexakisphosphate) impact uptake and translocation of heavy metals, the metabolic pathway of myo-inositol and the detoxification function of its downstream products may be modified in response to Cd (Cong et al, 2013). In Mesembryanthemum crystallinum exposed to Cu, heat shock protein 60 (HSP 60), which may participate in protein folding following exposure to denaturing conditions caused by stress, was recorded to increase ten-fold compared with controls (Thomas et al, 1998).…”
Section: Osmoprotectantsmentioning
confidence: 99%
“…significantly modulates the mRNA expression of the CAT2 gene and not CAT1 gene in Suaeda salsa, a pioneer halophyte(Cong et al 2013). In Suaeda salsa, the CAT2 gene was reported to play a major role in increased CAT activity under Cd stress and has been considered as a gene marker to indicate Cd pollution(Cong et al 2013). Studies have also been done to elucidate the alteration in the expression of CAT genes under metal(oid) stress.…”
mentioning
confidence: 99%
“…salsa were ground in liquid nitrogen. RNA extraction and synthesis of the fi rst strand cDNA were carried out as described previously (Cong et al, 2013). Based on the conserved motifs found in PCS proteins collected from the National Center for Biotechnology Information, degenerate primers were designed using the iCODEHOP program (Boyce et al, 2009).…”
Section: Homologous Cloning Of the Full-length Cdna Of Sspcsmentioning
confidence: 99%